NATURE OF APPLICATION REDUCTION THROUGH USING GENE USING MICROSOFT VISUAL BASIC 6.0 - Surya Darma; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2007)
This writing describes the application properties decrease Crosses Through Gen.Basically application Nature Through Crosses decline this gene is to determine whatproperties that will appear on the first descent, and when the offspring mated orcrossed each other then what properties will appear in the offspring of both. To thewriter wants to display them in computerized form by using Microsoft Visual Basic6.0. By presenting it in the form of computerized author hopes that the data we obtaina more accurate or the possibility of error becomes smaller.